Challenges in the implementation of patient security culture in Brazil: integrative literature review (Research, Society and Development, 2023)
Patient Safety consists of a set of actions aimed at preventing errors and adverse events in health care. Thus, implementing a safety culture demands the construction of values, attitudes and norms that guide the healthcare organization. Thus, the aim is to understand what are the challenges for the implementation of a patient safety culture in health care in Brazil. The construction of the research question adopted the Population, Concept and Context strategy and to answer it, searches were conducted in the PubMed/Medline, BVS Regional and Portal Capes databases, and seven articles were selected to compose the final study sample. The lack of training of care teams, lack of notification systems, as well as management support and a punitive culture to the occurrence of errors were identified as the main barriers to the implementation of the culture of safety in health care. Thus, the importance of recognizing the barriers to the implementation of safety culture as a strategy for the creation of improvement actions in the Brazilian health services in order to ensure adequate working conditions, training and supplies to the teams is evident.